2017
DOI: 10.1371/journal.pone.0173946
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis during partial carbonizing process of rhubarb, moutan and burnet

Abstract: Control of temperature and duration of partial carbonization for Chinese medicines have been mainly based on experience of the processors. No quantitative methods and parameters are available that can be used to precisely control the temperature and determine the energy changes during the process. In our research, with a simulated atmosphere air condition, the partial carbonization processes of three Chinese herb medicines rhubarb, moutan and burnet were simulated at different heating rates (5, 10 and 20°C • m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Previously, we used TG/DTG methods to simulate the processing procedure of Zushima, in order to qualitatively demonstrate the overall compositional changes [10,11], and also analyzed the effects of pyrolysis in an inert Ar atmosphere on the preparation of gallic acid, rhubarb, mudan and burnet [12]. We also calculated the energy dynamics during the stir-frying process based on the data obtained from thermal analysis techniques [13]. These applications have greatly enhanced our experimental and theoretical understanding of the processing procedures of traditional Chinese medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we used TG/DTG methods to simulate the processing procedure of Zushima, in order to qualitatively demonstrate the overall compositional changes [10,11], and also analyzed the effects of pyrolysis in an inert Ar atmosphere on the preparation of gallic acid, rhubarb, mudan and burnet [12]. We also calculated the energy dynamics during the stir-frying process based on the data obtained from thermal analysis techniques [13]. These applications have greatly enhanced our experimental and theoretical understanding of the processing procedures of traditional Chinese medicines.…”
Section: Introductionmentioning
confidence: 99%
“…The mass conversion rates in the temperature from 200 to 450 °C were 74.13% (5 °C min −1 ), 71.72% (10 °C min −1 ), 66.87% (15 °C min −1 ), and 65.76% (20 °C min −1 ), respectively. Previous researches have demonstrated that the lower heating rate, the more compounds in the materials combusted and pyrolyzed because the constituents in herb medicine have sufficient time to react [13]. The peak 2 and peak 3 were known as oxidative pyrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal analysis has been used as a method for evaluating the process technology of Chinese medicine in recent years [12]. This technology could provide various data to researchers including thermal gravimetry (TG), differential thermal analysis (DTA), derivative thermogravimetry (DTG), dynamic mechanical analysis (DMA), and thermo-mechanical analysis (TMA) for studying the changes of drugs during frying [13]. FTIR is one of the widely used methods for elucidating and identifying the components in herb medicine, and providing the date for the properties of the constituents in TCM [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This positive trend may be explained by the most favorable features of electromagnetic induction heating in that a uniform heating across the whole of the extraction vessel can be achieved in a few seconds leading to a massive and rapid release of secondary metabolites from plant cells and preventing their chemical degradation, pending a short-lasting process being applied. Furthermore, this is particularly true in the case of anthraquinones from Chinese rhubarb, for which it has been demonstrated that heating represents an effective means to increase their extractive yields from rhizome [ 9 ].…”
Section: Resultsmentioning
confidence: 99%